Combined interdiffusion and self-diffusion analysis in Al-Cu liquid diffusion couple. (15th January 2018) - Belova, I.V.; Heuskin, D.; Sondermann, E.; Ignatzi, B.; Kargl, F.; Murch, G.E.; Meyer, A.
Abstract: In this paper, a recent combined isotope and interdiffusion analysis is adapted to the case of binary liquid alloys. Shear-cell interdiffusion experiments with a layer enriched in 65 Cu sandwiched between the interdiffusion couple ends have been performed on liquid Al-Cu that is suitable for demonstration of the application of this analysis. (Note that the analysis is not limited to the use of the shear-cell technique.) The self-diffusion coefficient of Cu is then obtainable as a function of composition. Results of the new analysis are in good agreement with an independently measured Cu self (tracer) diffusion coefficient at two compositions. Graphical abstract: Image 1